Beyond Anthropocentrism: Reinterpreting Islamic Legal Ethics through Transspecies Rights and Ecological Jurisprudence - Hovhannes Sargsyan; Annisatul Maulidiyyah Rahman; Alice Björnsson; Yusuf Ndong Nzé; Ana Sofía del Carmen (Postgraduate Programme of UIN Kiai Haji Achmad Siddiq Jember, 2025)
Contemporary Islamic legal discourse predominantly adheres to an anthropocentric paradigm, marginalizing the moral and legal status of non-human entities. This study critically interrogates the philosophical and normative foundations of Islamic legal ethics by expanding the rights discourse through a transspecies lens. Employing an interdisciplinary approach—integrating ecological philosophy, moral rights theory, and transformative interpretations of maqashid syariah—this research reconceptualizes key concepts in Islamic jurisprudence, including life, agency, and ethical responsibility. Through a hermeneutical analysis of classical and contemporary Islamic texts, the study demonstrates how broadening the scope of rights beyond human subjects can fundamentally reshape Islamic legal thought. The findings reveal that a transspecies perspective not only enriches Islamic legal philosophy but also fosters a holistic jurisprudential framework that aligns with ecological ethics and sustainability principles. By integrating insights from environmental ethics, animal rights philosophy, and Islamic legal theory, this study challenges anthropocentric paradigms and offers a transformative vision for the ethical foundations of Islamic jurisprudence. Ultimately, this research contributes to broader discussions on legal pluralism, environmental ethics, and the reinterpretation of religious normative frameworks in addressing contemporary ecological crises.​​​​​​​​​​​​​​​